Clinical Characteristics and Outcomes of Dengue-infected Children Admitted to the Chiang Mai University Hospital During an Outbreak in 2008 - Tavitiya Sudjaritruk (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).